Don Dunstan : intimacy & liberty : a political biography - Hodge, Dino, 1957- (Kent Town, South Australia : Wakefield Press, 2014)
This book records the change in public discourse over issues of homosexuality - from morality to state security and then civil liberties. Don Dunstan worked as a member of parliament for more than twenty-five years, and then throughout the remainder of his life, to realise his vision of full equality for same-sex attracted citizens.
Includes bibliographical references (pages 332-399) and index.
Keywords: Dunstan, Don, -- 1926-1999.; Australian Security Intelligence Organisation; Premiers -- South Australia -- Biography; Politicians -- South Australia -- Biography; Statesmen -- South Australia -- Biography; Homosexuality -- Law and legislation -- Australia -- History; Police -- South Australia -- History; South Australia -- Politics and government -- 1945-; South Australia -- Politics and government -- 1965-